2021
DOI: 10.3390/ijms222011154
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Dysfunction in Inherited Cardiomyopathies

Abstract: Inherited cardiomyopathies form a heterogenous group of disorders that affect the structure and function of the heart. Defects in the genes encoding sarcomeric proteins are associated with various perturbations that induce contractile dysfunction and promote disease development. In this review we aimed to outline the functional consequences of the major inherited cardiomyopathies in terms of myocardial contraction and kinetics, and to highlight the structural and functional alterations in some sarcomeric varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 200 publications
(215 reference statements)
0
6
0
Order By: Relevance
“…We ltered the data by dbSNP database, 1000genomes database, ExAC and GnomAD database to screen out known variants, and found that both FLNC T407N and FLNC R437L sites were not reported and belonged to rare mutations; among them, FLNC T407N was evaluated to be low risk and generally conserved, and was excluded for the time being. FLNC T834M , FLNC R1567Q and FLNC V1253I were found in both DCM and control groups and considered as polymorphic site, among which FLNC V1253I was poorly conserved and therefore excluded; nally, four FLNC variants were screened as FLNC R437L , FLNC V452M , FLNC G1264S and FLNC L2538F , which corresponded to sequencing numbers (53,18,103,108), were all missense variants in DCM patients (Table 5).…”
Section: Clinical Characteristics and Sequencing Kurtosis Results Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We ltered the data by dbSNP database, 1000genomes database, ExAC and GnomAD database to screen out known variants, and found that both FLNC T407N and FLNC R437L sites were not reported and belonged to rare mutations; among them, FLNC T407N was evaluated to be low risk and generally conserved, and was excluded for the time being. FLNC T834M , FLNC R1567Q and FLNC V1253I were found in both DCM and control groups and considered as polymorphic site, among which FLNC V1253I was poorly conserved and therefore excluded; nally, four FLNC variants were screened as FLNC R437L , FLNC V452M , FLNC G1264S and FLNC L2538F , which corresponded to sequencing numbers (53,18,103,108), were all missense variants in DCM patients (Table 5).…”
Section: Clinical Characteristics and Sequencing Kurtosis Results Of ...mentioning
confidence: 99%
“…Cardiomyopathies are life-threatening diseases in which DCM is the ultimate phenotype of multiple mutations in heterogeneous pathways, including components of the membrane scaffolding apparatus, myosin, nuclear membrane proteins, calcium-processing proteins, transcription factors, and RNA splicing to cellular energy production mechanisms. Although these mutations are highly diverse in the affected pathways, they share the common features of impaired contraction and insurmountable cellular damage, leading to cell death and brotic repair, and ultimately contributing to cardiac thinning and dilatation [11,53]. FLNC is considered a key factor in the progression of different types of cardiomyopathies; therefore, determining the genetic and physiological roles of FLNC is necessary to determine the onset and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The troponin complex is associated with a structure called the sarcomere, which is the basic unit of muscle contraction. It complexly contributes to the regulation of contraction of the cardiac muscle ( 12 ). Therefore, troponin I is useful in the diagnosis of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…HCM-causing mutations are found in cardiac isoforms of myosin (MYH6/7/8), MyBP-C (MYBPC3), TnI (TNNI3), TnT (TNNT2), TnC (TNNC1), actin (ACTC1), Tm (TPM1), and MLC (MYL2) [151][152][153]. There are more than 1400 known mutations linked to HCM in these genes with myosin, MyBP-C, TnI, and TnT accounting for the majority of mutations [146].…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%